The Deeds of Suppiluliuma as Told by His Son, Mursili II - Güterbock, H. G.
Introduction — Reconstruction of the Text: First to Third Tablets; Further Fragments; “Seventh” Tablet; Isolated and Doubtful Fragments; Places of Discovery of the Tablets; Autographed Text; Transliteration and Translation.